2007
DOI: 10.1371/journal.pone.0000638
|View full text |Cite
|
Sign up to set email alerts
|

Simple PCR Assays Improve the Sensitivity of HIV-1 Subtype B Drug Resistance Testing and Allow Linking of Resistance Mutations

Abstract: BackgroundThe success of antiretroviral therapy is known to be compromised by drug-resistant HIV-1 at frequencies detectable by conventional bulk sequencing. Currently, there is a need to assess the clinical consequences of low-frequency drug resistant variants occurring below the detection limit of conventional genotyping. Sensitive detection of drug-resistant subpopulations, however, requires simple and practical methods for routine testing.MethodologyWe developed highly-sensitive and simple real-time PCR as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
79
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 17 publications
1
79
0
Order By: Relevance
“…The fitness cost of individual RT resistance mutations is well established, particularly for 215Y, 184V, and 65R (5). The transmission of any of the resistant variants more frequently associated with a fitness impairment might be associated with a more rapid reversion to a more "fit," WT genotype that might fail to be detected by conventional sequencing (17). Further studies are needed to determine whether these traditionally less fit variants are uniformly replaced at a significantly higher rate than other variants associated with higher RC values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fitness cost of individual RT resistance mutations is well established, particularly for 215Y, 184V, and 65R (5). The transmission of any of the resistant variants more frequently associated with a fitness impairment might be associated with a more rapid reversion to a more "fit," WT genotype that might fail to be detected by conventional sequencing (17). Further studies are needed to determine whether these traditionally less fit variants are uniformly replaced at a significantly higher rate than other variants associated with higher RC values.…”
Section: Discussionmentioning
confidence: 99%
“…The spontaneous appearance of drug resistance mutations in 3 of 14 patients (01-0512, 01-0550, and 01-0575) in the absence of selective drug pressure was most likely related to the presence of these particular resistant variants as relatively minor populations at the time of transmission, below the threshold of assay detection. More sensitive real-time PCR methods for detecting lowfrequency minor variants among treatment-naive individuals have shown that resistant variants identified by real-time PCR and missed by conventional sequencing may represent 0.7% to 11% of the population by clonal sequencing (17). Potential selective advantages may have resulted in the emergence of these resistant isolates over time to detectable levels despite the absence of selective drug pressure.…”
mentioning
confidence: 99%
“…Various ligation-mediated methods were consequently developed to detect point mutations in infectious and noninfectious circumstances, including Oligonucleotide Ligation Assay 14,15 and Ligation Amplification assay. 16,17 Other quantitative PCR-based detection techniques, such as allele-specific PCR (ASPCR) 18 and variations of multiplexing PCR assays, 19 depend on the retarded activity of DNA polymerase to extend on templates when there is a primer mismatch at the 3 0 end. However, all ligation-mediated methods and ASPCR are DNA based, requiring initial reverse transcription of RNA to cDNA.…”
mentioning
confidence: 99%
“…Point mutation assays, such as allele-specific PCR, can detect DRM at frequencies as low as 0.01% of the sampled viral population (31,45,53,54), but they do not provide information about the sequence context surrounding a given DRM and may be prone to false positives at the lower level of detection (22). High-resolution sequencing techniques, such as single genome sequencing (SGS) and ultradeep sequencing (UDS), permit analyses of DRM in the context of the surrounding genetic sequence and this allows the investigation of accessory mutations (AM) that are often associated with DRM during DRM selection (50).…”
mentioning
confidence: 99%